2022
DOI: 10.1039/d2cc01016j
|View full text |Cite
|
Sign up to set email alerts
|

High turnover photocatalytic hydrogen formation with an Fe(iii) N-heterocyclic carbene photosensitiser

Abstract: The first high turnover photocatalytic hydrogen formation reaction using an earth-abundant iron photosensitiser is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 35 publications
1
21
0
1
Order By: Relevance
“…This can primarily be attributed to two of its inherent advantages, as was shown in the recent development of an HER using an iron PS in combination with different proton reduction catalysts. 24 There, a measurement time of 25 s was used and three replicates were recorded, resulting in a total measurement time of less than 1.5 min per sample, while obtaining reliable data for each measurement (RSD ¼ 1%). As a result of the short analysis time, the main factor limiting the number of reactions performed and tracked in parallel when choosing not to trace in situ is the irradiation set-up itself, wherein only a certain number of reaction vials can be irradiated simultaneously, and not the analysis method.…”
mentioning
confidence: 99%
“…This can primarily be attributed to two of its inherent advantages, as was shown in the recent development of an HER using an iron PS in combination with different proton reduction catalysts. 24 There, a measurement time of 25 s was used and three replicates were recorded, resulting in a total measurement time of less than 1.5 min per sample, while obtaining reliable data for each measurement (RSD ¼ 1%). As a result of the short analysis time, the main factor limiting the number of reactions performed and tracked in parallel when choosing not to trace in situ is the irradiation set-up itself, wherein only a certain number of reaction vials can be irradiated simultaneously, and not the analysis method.…”
mentioning
confidence: 99%
“…Transient absorption spectroscopy furthermore confirmed that the quenching occurs by reductive electron transfer producing stable 2 (Figure 4) with a quantum yield hqhce of about 9 % (Table S16). Notably, the lower yield of quenching implied by the short lifetime is balanced by a cage escape yield hce > 20 % that largely exceeds the very moderate values previously found for the quenching of the 2 LMCT state of [Fe(III)(phtmeimb)2] + in acetonitrile 30,37 . PS (t0 /ps)…”
Section: Reductive Quenching Route and Consecutive Photo-induced Elec...mentioning
confidence: 62%
“…Notably, the lower yield of quenching implied by the short lifetime is balanced by a cage escape yield η ce > 20% that largely exceeds the very moderate values previously found for the quenching of the 2 LMCT state of [Fe( iii )(phtmeimb) 2 ] + in acetonitrile. 30,37…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations